Construction of the Responsibility of Pharmaceutical Corporation Directors in the Distribution of Narcotics Precursor Deviations - Tri Andika Syam; Faisal Santiago (CV. Green Publisher Indonesia, 2026)
The management of narcotics precursors places pharmaceutical corporations in a strategic position, given the legal authority to produce and distribute substances with a high risk of abuse. Law enforcement practices demonstrate that deviations in precursor distribution are often understood as technical violations or the actions of operational-level individuals, while the role of directors as strategic policymakers is rarely addressed by criminal liability. This situation creates a gap between the corporate control structure and the construction of legal accountability applied. This study aims to analyze the accountability practices of pharmaceutical corporation directors in deviations in the distribution of narcotics precursors and to formulate a more accountable and prevention-oriented legal reconstruction. The method used was normative legal research with a statutory and conceptual approach, accompanied by an analysis of the doctrine of corporate criminal liability, fiduciary duty, and corporate governance. The results show that normative weaknesses, the dominance of conventional evidentiary approaches, and excessive protection of business decisions have created room for impunity for directors. The proposed reconstruction positions directors as subjects of structural accountability through the recognition of active and passive responsibility, the use of objective parameters of error, and the affirmation of compliance system failures as the basis for criminal liability. This construction is expected to strengthen the effectiveness of narcotics law enforcement, increase compliance of pharmaceutical corporations, and provide more optimal protection for public health and security interests